2022
DOI: 10.1007/s40120-022-00361-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Risk Factors for Alzheimer’s Disease in Patients with Down Syndrome and Their Association with Brain Changes: A Narrative Review

Abstract: Several recent epidemiological studies attempted to identify risk factors for Alzheimer’s disease. Age, family history, genetic factors (APOE genotype, trisomy 21), physical activity, and a low level of schooling are significant risk factors. In this review, we summarize the known psychosocial risk factors for the development of Alzheimer’s disease in patients with Down syndrome and their association with neuroanatomical changes in the brains of people with Down syndrome. We completed a comprehensive review of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 122 publications
3
12
0
Order By: Relevance
“…Our study confirmed the link between hippocampal volume reduction and deficits in language functions and working memory (see figure 20), which has been reported widely by previous studies (Raz, Torres et al 1995, Krasuski, Alexander et al 2002, Pennington, Moon et al 2003. These findings reflect the role of the hippocampus as an essential biomarker for AD and one of the regions severely affected by the neuropathological changes of AD (Aylward, Li et al 1999, Hamadelseed, Elkhidir et al 2022. We found no significant correlation between age and hippocampal volume.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirmed the link between hippocampal volume reduction and deficits in language functions and working memory (see figure 20), which has been reported widely by previous studies (Raz, Torres et al 1995, Krasuski, Alexander et al 2002, Pennington, Moon et al 2003. These findings reflect the role of the hippocampus as an essential biomarker for AD and one of the regions severely affected by the neuropathological changes of AD (Aylward, Li et al 1999, Hamadelseed, Elkhidir et al 2022. We found no significant correlation between age and hippocampal volume.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results confirmed the association between temporal lobe volume reduction and deficits in working memory (see figure 20). This finding ensures the temporal lobe's role in memory function (Galaburda and Schmitt 2003, Pennington, Moon et al 2003, Vicari 2006, Menghini, Costanzo et al 2011, Mullins, Daly et al 2013, Hamadelseed, Elkhidir et al 2022) (see figure 9). Our results could not confirm the involvement of the temporal lobe in language deficits.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Down syndrome (DS) is the most common genetic cause of intellectual and developmental disability (IDD) resulting from the presence of an extra copy of chromosome 21 [ 1 , 2 ]. Globally, there are approximately 1:1000 to 1:1100 live births of people with DS [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a developmental approach, a better understanding of the developing brain with DS will illuminate important neurological principles of DS in children and shed light on the foundations of adult phenotypes, particularly the increased risk of early Alzheimer's disease (AD) (Lee et al., 2015; Zigman & Lott, 2007). Furthermore, investigating DS helps us study the early stage of AD, as DS can provide a suitable pattern for understanding AD pathology and clinical features at an early age (Delabar et al., 1990; Hamadelseed et al., 2022; Hartley et al., 2015; Lott & Head, 2019; Mann, 1988).…”
Section: Introductionmentioning
confidence: 99%